Use of Fermented Fish Ensilage in the Diets of Etroplus suratensis (Bloch) - N., Neethiselvan; G., Indira Jasmine; D., Manikandavelu; V.K., Venkataramani (Fishery Technology, 2025)
A feeding experiment was conducted to assess the ability of Etroplus sumtetisis (Bloch) to utilize diets containing fish ensilage as a major protein source. Attempt was also made to find out whether the neutralization of the fermented ensilage influenced the growth of Â£. suratensis or not. No significant difference in the survival rate of fish fed with various feeds was noticed (P(0.05). However, significant difference could be observed in specific growth rate,(P